Generation and Characterization of a Functional Nanobody Against Inflammatory Chemokine CXCL10, as a Novel Strategy for the Treatment of Multiple Sclerosis - Sadeghian-Rizi, Tahereh; Behdani, Mahdi; Khanahmad, Hossein; Sadeghi, Hamid M.; Jahanian-Najafabadi, Ali (CNS & Neurological Disorders - Drug Targets, 2019)
Background & Objective: Chemokines and their receptors play a pivotal role in the pathogenesis of various autoimmune diseases such as multiple sclerosis, infectious diseases, and also in cancer metastasis via attraction of the pathogenic immune cells into the inflammation sites. Methods: Inflammatory chemokine CXCL10 as a T helper (Th)1-chemokine directs chemotaxis of many cell subsets especially Th1 into the central nervous system (CNS) via its receptor CXCR3 and it has been put forward as a potential therapeutic target in the treatment of multiple sclerosis. Nanobodies are the smallest intact antigen binding fragments derived from heavy chain-only antibodies occurring in camelids with unique biochemical and biophysical features which render them superior to conventional antibodies or antibody fragments. Here, we describe the generation, selection, and characterization of CXCL10-specific Nanobodies from camel immunized with CXCL10. The obtained Nanobodies displayed high affinity towards CXCL10 about 10-11-10-8 M. Results: Then a Nanobody with the highest affinity named 3Nb12 was selected and investigated as a migration inhibitor of CXCR3+ cells. Chemotaxis assay results showed that 3Nb12 blocked CXCL10- CXCR3 binding and potently inhibited chemotaxis of CXCR3-transfected HEK293T cells. Conclusion: The nanobody 3Nb12 might be a promising specific and powerful blocking agent of CXCL10 function, which can be used for diagnostic, therapeutic and research purposes in MS.
Keywords: Nanobody